Awareness of, willingness to use, and experiences with Pre-exposure prophylaxis among youth in Nigeria - Titilola Gbaja-Biamila; Chisom Obiezu-Umeh; Ucheoma Nwaozuru; Nora E. Rosenberg; Mesoma Igbokwe; David Oladele; Adesola Z. Musa; Ifeoma Idigbe; Donaldson Conserve; Suzanne Day; Kadija Tahlil; Jason Ong; et al. (BMC, 2024)
Abstract Background Youth (ages 14-24) in Nigeria have disproportionately high rates of new HIV infection. Pre-exposure prophylaxis could substantially reduce new infections among youth but has not been scaled up. This cross-sectional study aimed to assess Pre-exposure prophylaxis awareness, willingness to use, and prior use of Pre-exposure prophylaxis among youth in Nigeria. Methods This is a secondary analysis of cross-sectional data from a quasi-experimental pilot study (clinical trial NCT04070287). The analysis focused on Pre-exposure prophylaxis awareness, willingness to use, and prior use among 324 youth recruited between September 2019 to March 2020. Descriptive statistics were calculated as frequencies and percentages for categorical variables and means and standard deviations for continuous variables. Results Of the 324 participants, the mean age and standard deviation were 21.17 (± 2.20) years. The majority were 20-24 years old (75.9%) and male (57.7%). Only 30.7% used condoms consistently over three months. Regarding Pre-exposure prophylaxis awareness and willingness, 62.6% had never heard of Pre-exposure prophylaxis, and 158 (50.1%) reported willingness to use Pre-exposure prophylaxis. Only 10 (3.2%) reported having used Pre-exposure prophylaxis. Conclusion Nigerian youth have low awareness of and prior use of Pre-exposure prophylaxis. Given the gap between prior use and willingness to use Pre-exposure prophylaxis, our findings suggest missed opportunities to prevent new HIV infections among youth in Nigeria. Efforts to increase awareness and uptake of Pre-exposure prophylaxis among this population should consider youth-led Pre-exposure prophylaxis outreach efforts and effectively communicate the benefits of Pre-exposure prophylaxis to this population. Trial Registration NCT04070287, the Date of registration of the trial is 20-07-2019.